2013
DOI: 10.1186/1472-6963-13-246
|View full text |Cite
|
Sign up to set email alerts
|

“A manager in the minds of doctors:” a comparison of new modes of control in European hospitals

Abstract: BackgroundHospital governance increasingly combines management and professional self-governance. This article maps the new emergent modes of control in a comparative perspective and aims to better understand the relationship between medicine and management as hybrid and context-dependent. Theoretically, we critically review approaches into the managerialism-professionalism relationship; methodologically, we expand cross-country comparison towards the meso-level of organisations; and empirically, the focus is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 43 publications
2
64
0
5
Order By: Relevance
“…It pays attention to the variations of the interrelationships among organisations, professions, practices and experiences on the meso‐level of organisations (Kuhlmann et al . , Wrede et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It pays attention to the variations of the interrelationships among organisations, professions, practices and experiences on the meso‐level of organisations (Kuhlmann et al . , Wrede et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…, Kuhlmann et al . , McDonald ). The professionals respond differently to changing policy and governance arrangements and governments may utilise the professional experts strategically as a governance tool (Burau ).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure comparability between sites and between countries, a consistent data analysis approach was developed. During the data collection and analysis, researchers discussed issues emerging from data collection and intermediate results at monthly online meetings and during two face-to-face workshops [31, 32]. At the first workshop, researchers were updated on the approaches to take in interviewing and observation.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrently, empirical studies have identified medically informed managers who function as a “hybrid,” successfully bringing professionalism and managerialism together . However, this has mainly been studied with hybrid managers in focus, exploring their abilities to articulate economic efficiency requirements in relation to clinical work and to adapt communication to professional culture .…”
Section: Introductionmentioning
confidence: 99%